American baseball fans do not influence game outcomes - Zimmer, T. E.; Snyder, A.; Bukenya, L. (Economics Bulletin, 2021)
The paper examines U. S. Major League Baseball (MLB) data to evaluate home-field advantage and the relationship between fan attendance and game outcomes. Due to the COVID-19 pandemic, fans were not allowed in stadiums during the 2020 MLB regular season. The results indicate the absence of fans did not statistically alter home-field advantage when controlling for quality of play.